Commercial bank credits and industrial development in Nigeria - Njoku, Charles Odinakachi; Ugwu, Kelechi Enyinnia; Nwaimo, Chilaka Emmanuel; Ezekiel, Obumneme Daniel (Journal of Commerce, Management, and Tourism Studies, 2023)
The aim of this study is to determine how credit from commercial banks affects Industrial Growth in Nigeria. The study spans the years 1983 through 2020. For this reason, Commercial Bank Credits was divided into Commercial Banks Credit to the Manufacturing Sector (CBMF), Commercial Banks Credit to the Mining Sector (CBMN), and Commercial Banks Credit to the Real Estate and Construction Sector (CBRC), and their various effects on Industrial Development (Industrial Gross domestic product - IGDP) were taken into account. It was discovered that all the variables attained stationarity at the first and second difference and then freed themselves from the unit root tangle. The Johansen co-integration test results demonstrated that there is no co-integration equation between the variables listed in the model. The Granger Causality test, which was conducted, showed that there was only one causal relationship between Commercial Banks' contribution to the mining sector (CBMN) and Industrial Development (IGDP). According to the regression analysis's findings, there is a positive and significant relationship between commercial banks' lending to the manufacturing sector (CBMF) and industrial development (IGDP), as well as a negative and significant relationship between commercial banks' lending to the real estate and construction sector (CBRC) and industrial development. This suggests that there is a significant connection between Industrial Development and the credit offered by commercial banks. This research on the effect of Commercial Bank Credits on Industrial Development studied only the Nigerian case. So, the research recommends that this study be extended to other Sub Saharan African Countries.  In order to enhance industrial growth and development in the long run, it is recommended that, the commercial banks should grant medium and long term loans to the major players in the industrial sector and avoid under-lending or over-lending. There is disagreement regarding whether there is a long-term or short-term relationship between commercial bank credits and industrial development, as well as the direction of causality. The majority of researchers on this subject did not examine the nature and direction of the relationship between Commercial Bank Credits and Industrial Development in Nigeria using the Cointegration Test and Granger Causality Test. This study closes the knowledge gap.